Recognizing Perspectives: Narrative Differences and Hidden Ideologies in Taiwanese History Textbooks - Pei-Fen Sung; Ting Shiuan Ku (National Taipei University of Education, 2015)
Democratization allowed Taiwanese History to be established independently in the curriculum, and because Taiwanese consciousness and Chinese consciousness are two main historical ideologies in the history curriculum, there is a need for history teachers to have the ability to judge the underlying perspectives in Taiwanese History. This study utilizes three versions of Junior-high school Taiwanese history textbooks and examines three themes-- "The Origins of Taiwanese Aboriginals," "The Historical Relationship between Taiwan and China," and "the Mu-Dan-She Event" --to explain the narrative differences in the textbook accounts. We found Taiwanese consciousness, Chinese consciousness and international consciousness in the three different textbooks. However, these identity-related ideologies are embedded in historical facts that appear to be neutral making perspectives in the narratives unheeded. We believe that teachers need to help sensitize students with the underlying perspectives and interpretive frames in historical narratives in order to cultivate citizens' rational thinking ability and to develop discernment in identifying identity education hidden in textbooks in a democratic society.